A Kingdom of Water : Adaptation and Survival in the Houma Nation - D'Oney, J. Daniel (Book collections on Project MUSE., 2020)
"In A Kingdom of Water, J. Daniel d'Oney offers a political history of the United Houma Nation in Louisiana in a narrative that examines the nation's history after 1699. By focusing on survival and adaptation to French, Spanish, British, and American imperial control of their region, A Kingdom of Water examines how one Native American group successfully navigated a constantly changing series of political and economic landscapes between 1699 and 2005, all while maintaining their sense of identity"--